2001
DOI: 10.1002/j.1556-6676.2001.tb01979.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of a Prejudice Prevention Project

Abstract: This article reports on the effectiveness of a prejudice prevention intervention that was used among a culturally diverse group of students in Hawaii. Implications of the results of this primary prevention effort for counseling practice and interculturally adaptive social development are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…The findings of Salzman and D'Andrea (2001) and Malecki and Elliott (2002) indicated differences between student self-ratings of social skills and ratings of their social skills by teachers, which is consistent with the low observed correlations between these raters in the SSRS standardization data. Crowley and Merrell's (2000) findings also are consistent with previous studies in that observed relationships with measures of internalizing problems were negative and ranged from small to moderate.…”
Section: Evidence From Studies Using the Ssrs-student Elementary Formsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings of Salzman and D'Andrea (2001) and Malecki and Elliott (2002) indicated differences between student self-ratings of social skills and ratings of their social skills by teachers, which is consistent with the low observed correlations between these raters in the SSRS standardization data. Crowley and Merrell's (2000) findings also are consistent with previous studies in that observed relationships with measures of internalizing problems were negative and ranged from small to moderate.…”
Section: Evidence From Studies Using the Ssrs-student Elementary Formsupporting
confidence: 89%
“…Simultaneous collection of such data would provide insight as to the accuracy of student self-ratings in detecting developmental changes (or lack thereof ) in social skills over time. This type of study would have particular relevance for intervention research (e.g., Salzman & D'Andrea, 2001) employing student self-reported social skills as a dependent variable.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformative interventions tend to be more intensive and structured, and use a number of media and activities such as art, games, and drama to tackle different aspects of prejudice (e.g. Salzman & D'Andrea, 2001;see Bigler, 1999 for review). Others have recommended that multicultural education should follow a 'whole school' approach, whereby the entire school adopts a multicultural ethos, and multiculturalism is evident in all aspects of school life, for instance in wall displays, games, and all lessons including geography and social studies as well as other subjects such as maths and domestic science (Knowles & Ridley, 2006).…”
Section: Interventions Developed By Educatorsmentioning
confidence: 99%
“…Books published in other countries can provide authentic accounts of the people, history, and traditions of other lands and help to counteract stereotypes and the often more sensation-prone information provided through television or other media [17]. And yet, most libraries in the United States have inadequate foreign language collections.…”
Section: Introductionmentioning
confidence: 99%